The balanced scorecard approach as a web site evaluation tool : a qualitative analysis of 5-star lodges in South Africa - Van Heerden, Cornelius Hendrik, 1957- (University of Pretoria, 2013)
Dissertation (MCom)--University of Pretoria, 2010.